Dehydration enhances innate immunity in a semiaquatic snake from the wet‐dry tropics. Issue 4 (14th March 2019) - Brusch, George A.; Christian, Keith; Brown, Gregory P.; Shine, Richard; DeNardo, Dale F.
Abstract: Dehydration is considered a physiological challenge, and many organisms live in environments that undergo periods of reduced water availability that can lead to dehydration. Recent studies have found a positive relationship between dehydration and innate immune function in animals adapted to xeric or semixeric environments. To explore the generality of this relationship, we examined the impact of dehydration on innate immune performance in water pythons ( Liasis fuscus ), a semiaquatic snake from the wet‐dry tropics of Australia. We collected blood samples from male and female water pythons held in the laboratory without food and water for 4 weeks. We also collected blood from free‐ranging snakes throughout the Austral dry‐season. We evaluated plasma osmolality and innate immune function (agglutination, lysis, and bacterial‐killing ability) and found that increased osmolality, whether manipulated in the laboratory or as a result of natural water limitation, resulted in enhanced aspects of innate immune performance. Counter‐intuitively, snakes in the wild became more hydrated as the dry season progressed, suggesting the dehydrated snakes move to water sources periodically to rehydrate. Comparing our data with those from previous studies, we suspect species divergence in the level of dehydration (i.e., hyperosmolality) that triggers enhanced immune capabilities. Abstract : Semiaquatic water pythons ( Liasis fuscus ) have enhanced innate immune abilities when dehydrated, regardless of the underlying reason (seasonal drought or experimental water deprivation). These results highlight that the newly discovered but poorly understood relationship between hydration and immune function exists even in a semiaquatic species.